2005
DOI: 10.1111/j.1467-9930.2005.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

General Deterrence and Corporate Environmental Behavior*

Abstract: This research addresses the assumption that “general deterrence” is an important key to enhanced compliance with regulatory laws. Through a survey of 233 firms in several industries in the United States, we sought to answer the following questions: (1) When severe legal penalties are imposed against a violator of environmental laws, do other companies in the same industry actually learn about such “signal cases”? (2) Does knowing about “signal cases” change firms’ compliance‐related behavior? It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 20 publications
7
151
0
1
Order By: Relevance
“…Numerous studies have demonstrated the importance of external motivators like regulatory enforcement and punitive sanctions in prompting regulated organizations not only to comply with law but to regulate themselves. Regulatory penalties can promote formal compliance with legal requirements (Gunningham, Thornton, and Kagan, 2005;Mendelhoff and Gray, 2005;Shimshack and Ward, 2005). Punitive enforcement can also motivate organizations to adopt self-regulatory structures and policies, at least symbolically (Edelman, 1992;Sutton et al, 1994;Short and Toffel, 2008).…”
Section: Effect Of Regulatory Threats On Commitments To Self-regulatementioning
confidence: 99%
“…Numerous studies have demonstrated the importance of external motivators like regulatory enforcement and punitive sanctions in prompting regulated organizations not only to comply with law but to regulate themselves. Regulatory penalties can promote formal compliance with legal requirements (Gunningham, Thornton, and Kagan, 2005;Mendelhoff and Gray, 2005;Shimshack and Ward, 2005). Punitive enforcement can also motivate organizations to adopt self-regulatory structures and policies, at least symbolically (Edelman, 1992;Sutton et al, 1994;Short and Toffel, 2008).…”
Section: Effect Of Regulatory Threats On Commitments To Self-regulatementioning
confidence: 99%
“…However, social oversight and acceptance may have different implications for particular actuarial risks depending on political context and the levels and contours of political risk. So, social oversight has, alternately, been argued to raise industry standards in some cases (for example, reducing pollution levels) (Gunningham et al 2005), while other studies point to a social licence being somewhat independent of actuarial concerns (Haines 2009) or even that social acceptance or a social licence (that is, successful sociocultural risk management) can be accompanied by ongoing and serious actuarial concerns (Bachrach and Baratz 1970;Culley and Hughey 2008).…”
Section: Risk Management and Regulationmentioning
confidence: 99%
“…There is also evidence of prosecuted enterprises implementing additional actions to manage risks (specific deterrence), but less evidence that prosecution of others prompts nonprosecuted enterprises to take appropriate preventive action (general deterrence), as communication of information about cases may be unreliable or differences in business operations may make comparisons difficult ( Jamieson et al 2010;Schofield et al 2009;Bluff 2015a;Thornton et al 2005). …”
Section: The Role Of State Whs Regulatorsmentioning
confidence: 99%
“…That issue was specifically examined by Thornton, Gunningham, and Kagan (2005). In their study, Thornton and colleagues asked corporate decision makers about their knowledge and responses to environmental penalties levied against other facilities.…”
Section: Empirical Assessments Of Deterrence and Environmental Crimementioning
confidence: 99%